Cannula provoked upper extremity superficial vein thrombophlebitis: are we overtreating?. Issue 11 (3rd November 2022) - Yuen, Hiu L. A.; Fang, Wendy; Tran, Huyen; Chunilal, Sanjeev D.
Abstract: Cannula provoked upper extremity superficial vein thrombophlebitis (UESVT) is common. Retrospective audit of 93 consecutive patients, 51% male, median age 57 years (range 20–91), with symptomatic UESVT revealed varied management including symptomatic management (37%), prophylactic (37%) and higher dose anticoagulation (27%). There was 2% (95% confidence interval (CI) 0–7.6) thrombus extension and 1% (95% CI 0–5.9) major bleeding, both limited to cancer. We argue anticoagulation is unnecessary in most UESVT patients.